1976
DOI: 10.1159/000180609
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chronic Progressive Glomerulonephritis with Immunofluorescent ‘Mesangial Pattern’ in Rats

Abstract: Morphologic changes of extracapillary and chronic progressive glomerulonephritis with contracted kidneys, resembling those of adult human chronic glomerulonephritis, were induced in rats by a single injection of the purified glycopeptide and Freund’s incomplete adjuvant into the hind footpads. The purified glycopeptide was prepared by TCA treatment or DEAE-cellulose chromatography from the nephritogenic glycopeptide which is known to have the ability to induce typical morphologic changes of membranous glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…Morphological changes in concurrent positive control group VI injected with natural nephritogenoside were those of chronic glomerulonephritis as those previously reported [6][7][8]. The careful examination led to the dis covery of myeloid bodies deposited in glomerular ep ithelial cells.…”
Section: Urinary Protein Excretionsupporting
confidence: 73%
See 3 more Smart Citations
“…Morphological changes in concurrent positive control group VI injected with natural nephritogenoside were those of chronic glomerulonephritis as those previously reported [6][7][8]. The careful examination led to the dis covery of myeloid bodies deposited in glomerular ep ithelial cells.…”
Section: Urinary Protein Excretionsupporting
confidence: 73%
“…We have previously reported that a single footpad injection of a homologous renal glycopeptide (called nephritogenoside) induces in rats mesangial proliferative glomerulonephritis (PGN) with a pattern of mesangial immunofluorescence [1][2][3][4], which results in sclerosing glomerulonephritis (end-stage kidney), 6-8 months after injection [5][6][7], This finding has been supported by Nishii et al [8].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously, strikingly similar results have been obtained in the experiments using renal glycopeptide that was isolated and purified from nephritogenic renal glycoprotein (ob tained from the trypsin digests) by further proteolytic digestion (72 h) with pronase [16][17][18], Consequently, the procedure -pronase di gestion followed by T C A treatment -seems to have an ability to isolate from rat kidney the glycopeplide that possesses no antigenic activ ity with respect to producing nephrotoxic anti body (kidney-fixing antibody), but has an abil ity when combined with Freund's incomplete adjuvant to induce proliferative glomerulo nephritis (with an immunofluorescenl mesan gial pattern) in rats (homologous animals) by a single injection into the hind footpads.…”
Section: Discussionsupporting
confidence: 62%